Clinical use of low haemoglobin density, transferrin saturation, bone marrow morphology, Perl's stain and other plasma markers in the identification of treatable anaemia presenting for cardiac surgery in a prospective cohort study. Issue 11 (1st July 2015) - Martin-Cabrera, Pedro; Hung, Matthew; Ortmann, Erik; Richards, Toby; Ghosh, Marcus; Bottrill, Fiona; Collier, Timothy; Klein, Andrew A; Besser, Martin W
Abstract : Objectives: The differential diagnosis between iron deficiency anaemia (IDA) and anaemia of chronic disease (ACD) with or without associated iron deficiency can be challenging. We assessed the use of different parameters, both classical like ferritin, transferrin saturation and stainable bone marrow iron stores, and novel markers such as low haemoglobin density (LHD) and hepcidin to help discriminate between the three entities. This would allow the detection of patients with ACD with associated iron deficiency, which could benefit from iron supplementation that would have otherwise remained undetected. Materials and methods: Prospective and observational cohort study from 2012 to 2013 where 200 anaemic cardiac surgical patients were recruited and 165 were studied. Detailed blood and bone marrow analyses were performed to establish the aetiology of anaemia. Results: Seventy-four patients (44.8%) had ACD and 29 (39%) of these had an elevated LHD indicating concomitant iron deficiency. Hepcidin was inappropriately normal or increased in the IDA and ACD group. Mean hepcidin was however lower in the group with IDA (4.8 ng/mL) than in the ACD group (15.0 ng/mL; p=0.002). Median hepcidin was lower in patients with ACD and iron restriction as indicated by LHD >4% (17.5 ng/mL) than on those with no iron restriction (25.9 ng/mL; p=0.045). In patients with ACD there was no concordance between Perl's stain and LHD. Conclusions: LHD was superior to hepcidin and bone marrow iron stores in identifying patients with ACD and associated iron deficiency, which would potentially benefit from parenteral iron therapy.